Calcific tendinopathy of supraspinatus tendon in elite volleyball players: A point-of-care ultrasound diagnosis - Corvino, A.; Corvino, F.; Liccardo, A.; Tafuri, D. (Journal of Human Sport & Exercise, 2021)
The sports in which there is the figure of goalkeeper, becomes relevant in order to obtain high performance, the perception of success that this participant is formed and that is configured as an expectation. Therefore, this study aims to analyse the association between perception of self-efficacy of two elite water polo goalkeepers and their coach and the observable performance in an international tournament. In order to measure the perception of behavioural success and their coach, it was used the Scale of achievement self-efficacy for water polo goalkeepers (Argudo, De la Vega, Tejero, & Ruiz, 2013). To measure the performance, were analysed all throwing`s received by the two goalkeepers in the XV Water polo World Championship. The results indicate that there are differences between the perception of the player, the coach and the observed behaviour, appreciating that the goalkeeper's perception of success is superior to what actually happens. While in the female case, player and coach perception is less than the observed behaviour.